Need of a journal club in every medical education setup - Singh, Harminder (International Journal of Basic & Clinical Pharmacology, 2017)
The scenario of scientific inscription has changed a lot with every day a new journal takes birth and so more and more manuscripts are written or manufactured in eagerness of academic endorsement/promotion, but very few academicians are appraising journals. This is a reality that the medical fraternity has exceptionally little curiosity in journal indulgent may be due to lack of proper training in this regards and the journal club (JC) is a reply to this need. Medical education workforce must develop the necessary skills to keep up with the vast amount of information available. The JC is an influential educational instrument and has played an active role in medical education for over a century. Even though, this tool has been included in the postgraduate program, there still remains a need of understanding the concept and importance of journals. This paper provides an inclusive appraisal about what a JC and how to acquire/establish it our departments.